The Impact of The BREXIT Referendum on European Union Immigrant Policy in UK - Haryadi, Resqita Trisya Nurtyandini (Jurnal Ilmu Hubungan Internasional LINO, 2022)
The problem of immigrants in the UK is caused by the policy implemented by the European Union, namely the Open Door Immigration Policy. This makes it difficult for Britain to control the immigrants who enter the country. The issue of immigrants has become one of the instruments echoed by supporters of the Brexit campaign as one of the reasons for pushing for Britain’s exit from the European Union. This article aims to analyze the impact of the Brexit referendum on the European Union Immigration Policy in the UK. This research uses a qualitative approach by reviewing literature from various secondary data sources. The theories used Regionalism and Immigrant theory. The results showed that The UK plans to adopt Australia’s policy of competing for EU and non-EU immigrants to enter the country.